2004
DOI: 10.1590/s0103-97332004000300011
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of quasi small-world nanomaterials

Abstract: The possibility of materials that are governed by a fixed point related to small world networks is discussed. In particular, large-scale Monte Carlo simulations are performed on Ising ferromagnetic models on two different small-world networks generated from a one-dimensional spin chain. One has the small-world bond strengths independent of the length, and exhibits a finite-temperature phase transition. The other has small-world bonds built from atoms, and although there is no finite-temperature phase transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…This study is motivated by physical small-world networks [22][23][24] where the number of short-cut bonds (which are SW bonds) cannot grow as fast as N. In [22,23] it was shown that the properties of such systems for small N can nevertheless show some of the mean field properties of a full small-world system. Fig.…”
Section: Results and Scaling: Sw-modelmentioning
confidence: 99%
See 4 more Smart Citations
“…This study is motivated by physical small-world networks [22][23][24] where the number of short-cut bonds (which are SW bonds) cannot grow as fast as N. In [22,23] it was shown that the properties of such systems for small N can nevertheless show some of the mean field properties of a full small-world system. Fig.…”
Section: Results and Scaling: Sw-modelmentioning
confidence: 99%
“…There are two ways to obtain physical SW networks [22][23][24] to study the effect of SW bonds that can be built from physical building blocks. These physical SW networks must satisfy certain constraints so that they can be built from physical building blocks.…”
Section: Results and Scaling: Physical Sw-modelmentioning
confidence: 99%
See 3 more Smart Citations